Getting started with cybersecurity science - Dykstra, Josiah (O'Reilly, 2015)
"Creating, using, and evaluating cybersecurity tools and systems are complex tasks. Cybersecurity professionals are attracted to these challenges and motivated to use their expertise to bring sanity and solutions to real world problems. Applying science to this process is often relegated solely to academics in ivory towers. This webcast will provide an introduction and practical information about how you can use science to understand and improve the tools you build and use everyday. Whether you're a student, software developer, forensic investigator, network administrator, or have any other role in providing cybersecurity, you'll learn about the relevant scientific principles and flexible methodologies for effective cybersecurity. This webcast will focus on real-world applications of science to your role in providing cybersecurity. You'll learn about why science is worth the added effort, how to develop your own cybersecurity experiments, and insights from specific examples of experimentation in cybersecurity."--Resource description page.